Pengaruh Tingkah Laku Etika Ketua Terhadap Tingkah Laku Subordinat di Sektor Kewangan Di Malaysia - Abdullah, Haji Abdul Ghani (2000)
The objectives of the study are multifold: (1) to investige the relationship and differences between leaders ethical behaviour and subordinates’ ethical behaviour; (2) to identify factors that moderate the relationship; (3) to examine the differences and the relationship between the degree of belief of the leader and that of the subordinates; and (4) to determine the main sources of their beliefs. This study is limited to all banks in Kedah and Perlis. Leader’s and subordinates’ ethical behaviours were treated as independent and dependent variables respectively. Subordinates’ and leader’s individual characteristics as well as situational factors were considered as moderators. Data from 77 pairs of leaders and their immediate subordinates were analysed. The results showed that we have not enough evidence to prove the influence of leader’s ethical behaviour on their subordinates’ ethical behaviour. However, the leader’s ethical behaviour appeared to have the tendency to explain the variance of subordinates’ ethical behaviour negatively. We found that leader’s and subordinates’ ethical behaviours are significantly different. Their Defining Issue Test (DIT) scores are 67.39 and 57.14 respectively. The finding also indicates that the degree of subordinates’ belief, their religious stance, their degree of exposure to ethics related subject during the subordinates study and during their work, the leadership style, the social responsibility of leader, and the organisational ethical culture practices directly influence subordinates’ ethical behaviour. Furthermore, the study also found that subordinates’ belief and leadership style significantly moderated the influence of leader’s ethical behaviour on subordinates’ ethical behaviour. Mean scores of leader’s and subordinates’ beliefs are 4.05 and 3.44 respectively. The results of the study reveal that information source is the strongest source of the belief, relative to descriptive and inferencing sources. In addition, the study implies the need for formal ethics related education among subordinates since it shows to have a positive influence on subordinates’ ethical behaviours. The findings of the present study also suggest that leaders should set an examplary model behaviours for their subordinates to follow.